2019
DOI: 10.1002/iub.2124
|View full text |Cite
|
Sign up to set email alerts
|

An immune infiltration signature to predict the overall survival of patients with colon cancer

Abstract: Immune infiltration of tumors has been increasingly accepted as a prognostic factor in colon cancer. Here, we aim to develop a novel immune signature, based on estimated immune landscape from tumor transcriptomes, to predict the overall survival of patients with colon cancer. The compositions of 22 immune cell subtypes from threeCIBERSORT, colon cancer, immune infiltration, prognosis, tumor microenvironment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 46 publications
2
47
0
Order By: Relevance
“…Macrophages were the most majority tumor immune-infiltrating cells in GBM, including M0, M1, and M2 cells. It is generally considered that M0 macrophages are unactivated and without specific function (19). While M0 can differentiate into M1 and M2 under different stimulations, and they, respectively, exhibit inflammatory response against tumor cells and immunosuppressive response promoting tumor cells proliferation and differentiation (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophages were the most majority tumor immune-infiltrating cells in GBM, including M0, M1, and M2 cells. It is generally considered that M0 macrophages are unactivated and without specific function (19). While M0 can differentiate into M1 and M2 under different stimulations, and they, respectively, exhibit inflammatory response against tumor cells and immunosuppressive response promoting tumor cells proliferation and differentiation (23).…”
Section: Discussionmentioning
confidence: 99%
“…LASSO Cox analysis, as a wildly used high-dimensional predictor regression method (18), selecting the optimal penalty parameter lambda using 10-fold cross-validations to prevent overfitting (19), can achieve shrinkage and variable identify simultaneously (20), and thus, which is an appropriate solution to establish signatures if there are numerous correlated covariates (21). Therefore, we utilized LASSO Cox regression analysis in the training set to establish an IIRPSS by a linear combination of selected prognostic cell compositions among 22 immune cell types weighted by the optimal coefficients.…”
Section: Construction An Immune Infiltration-related Prognostic Scorimentioning
confidence: 99%
“…Several studies based on the scRNA-seq of mouse lung tissue have already reported on the complexity of lung composition [29,32,[38][39][40]. Alternatively, some bioinformatic methods, such as CIBERSORT, can be used to characterize cell composition of complex tissues from their bulk transcriptome data [41] and have previously been successfully used to enumerate immune subsets in the tumor microenvironment [42][43][44][45][46][47]. CIBERSORTx, an updated version of CIBERSORT, is a machine learning method that can infer cell-type-specific gene expression profiles without physical cell isolation, as well as dissect large-scale tissue data using scRNA-seq data [28].…”
Section: Discussionmentioning
confidence: 99%
“…Misregulated RNA expression profiles, including autophagy‐related gene sets, 38 metabolism‐associated gene sets, 39 immune gene sets, 40 hypoxia‐associated gene sets, 41 microRNAs 42 and long non‐coding RNAs, 43 have all been shown to affect disease progression and prognosis in CRC. In this study, we demonstrated that dysregulation of RPGs could allow the stratification of CRC patients based on different outcomes.…”
Section: Discussionmentioning
confidence: 99%